2022
DOI: 10.21203/rs.3.rs-2292024/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Efficacy and Safety of Aripiprazole in Borderline Personality Disorder: A Systematic Review

Abstract: Introduction Aripiprazole is an atypical antipsychotic drug, and its use in the treatment of borderline personality disorder remains controversial. We aimed to determine the efficacy and safety of aripiprazole in patients diagnosed with borderline personality disorder. Methods The protocol was registered in PROSPERO (CRD42021256647) on July 2, 2021. PubMed, Scopus, Web of Science, Ovid-Medline, Embase, PsycINFO, and Cochrane (CENTRAL) were searched, without restriction by language or publication date. Furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 32 publications
(36 reference statements)
0
1
0
Order By: Relevance
“…It has been found to have good short-and long-term tolerability, less extra pyramidal side effects and less likely to modify the metabolic profile. [12][13] Previous research using both open-label and placebocontrolled designs has shown that aripiprazole is an effective additional treatment for depressive disorder. However, it is unknown which SSRI is the better option to be combined with aripiprazole.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found to have good short-and long-term tolerability, less extra pyramidal side effects and less likely to modify the metabolic profile. [12][13] Previous research using both open-label and placebocontrolled designs has shown that aripiprazole is an effective additional treatment for depressive disorder. However, it is unknown which SSRI is the better option to be combined with aripiprazole.…”
Section: Introductionmentioning
confidence: 99%